WAJAH POLITIK DAN BUDAYA TELEVISI MENJELANG PEMILU 2014 - Gufroni Sakaril (Jurnal Visi Komunikasi, 2014)
This article examines how factors of political economy of media in the democraticera influence on media content , in particular , how the political situation ahead of the 2014elections and how this political phenomenon is mediated by the media . Culture in the worldof television media that tend to promote market logic makes political events as entertainment. Pack the political news as a commodity for the sake of profit alone . Capital and power tomake the political reality is precisely to create capital .Artikel ini mengkaji bagaimana faktor-faktor ekonomi politik media pada erademokrasi memberikan pengaruh terhadap isi media, khususnya, bagaimana situasi politikmenjelang pemilu 2014 dan bagaimana fenomena politik ini dimediasikan oleh media.Budaya media dalam dunia televisi yang cenderung mengedepankan logika pasarmenjadikan peristiwa politik sebagai hiburan. Mengemas berita politik sebagai komoditasuntuk kepentingan profit semata. Modal dan kuasa menjadikan realitas politik justru untukmenciptakan kapital.